Ketidakpastian Hukum Keputusan Fiktif Positif Oleh Pejabat Pemerintahan Tata Usaha Negara - Tan Hana Darma Mangruwa Wati; Syofyan Hadi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Administrative Decisions of Government, also referred to as State Administrative Decisions (Keputusan Tata Usaha Negara/KTUN), are written decisions issued by Government Bodies and/or Officials in the administration of government affairs. This definition is stipulated in Article 1 point 7 of Law Number 30 of 2014 on Government Administration (UUAP). The regulation also amended the meaning of negative fictitious decisions as regulated in Article 3 of Law Number 5 of 1986 on State Administrative Courts (UUPTUN) into positive fictitious decisions as provided in Article 53 of the UUAP. A negative fictitious decision means that the silence of a government official regarding an application submitted by the public, after the lapse of the statutory time limit, is deemed as a rejection. Meanwhile, a positive fictitious decision means that the silence of a government official regarding an application submitted by the public, after the lapse of the statutory time limit, is deemed as an approval. Following the enactment of Law Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 on Job Creation into Law (UUCK), the regulation continues to recognize the concept of positive fictitious decisions. However, it abolishes the authority of the State Administrative Court (PTUN) to adjudicate fictitious State Administrative Decisions, which consequently gives rise to legal certainty issues for the public, particularly since the implementing Presidential Regulation has not yet been issued.This research employs a normative legal research method with a prescriptive approach. The results are expected to provide prescriptions regarding the legal issues examined.